Fiducial polarization observables in hadronic WZ production: a next-to-leading order QCD+EW study - Julien Baglio; Le Duc Ninh (Journal of High Energy Physics, 2019)
Abstract We present a study at next-to-leading-order (NLO) of the process pp → W ± Z → ℓν l ℓ ′+ ℓ ′−, where ℓ, ℓ′ = e, μ, at the Large Hadron Collider. We include the full NLO QCD corrections and the NLO electroweak (EW) corrections in the double-pole approximation. We define eight fiducial polarization coefficients directly constructed from the polar-azimuthal angular distribution of the decay leptons. These coefficients depend strongly on the kinematical cuts on the transverse momentum or rapidity of the individual leptons. Similarly, fiducial polarization fractions are also defined and they can be directly related to the fiducial coefficients. We perform a detailed analysis of the NLO QCD+EW fiducial polarization observables including theoretical uncertainties stemming from the scale variation and parton distribution function uncertainties, using the fiducial phase space defined by the ATLAS and CMS experiments. We provide results in the helicity coordinate system and in the Collins-Soper coordinate system, at a center-of-mass energy of 13 TeV. The EW corrections are found to be important in two of the angular coefficients related to the Z boson, irrespective of the kinematical cuts or the coordinate system. Meanwhile, those EW corrections are very small for the W ± bosons.